Analysis of Student Entrepreneurship decision making in the Learning Prerspective - Agus Syam; Sudarmi Sudarmi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
The main problem of entrepreneurship education in Indonesia is the mindset of most Indonesian people that the goal of continuing education to higher education to become a civil servant is not to be someone who has an entrepreneurial mentality. Entrepreneurship learning has not been able to change the mind-set of college graduates from finding jobs (job seekers) to creating jobs (job creators). Therefore, the formulation of the problem in this study is,